Hydrogen Sulphide and Nitric Oxide Cooperate in Cardioprotection Against Ischemia/Reperfusion Injury in Isolated Rat Heart - USTUNOVA, SAVAS (In Vivo, 2020)
Background/Aim: This study was designed to provide further evidence for the interactions between hydrogen sulfide (H(2)S) and nitric oxide (NO) in ischemia/reperfusion (I/R) injury. Materials and Methods: Rat hearts were studied with the Langendorff technique using the H(2)S donor sodium hydrosulfide (NaHS, 40 μM) and the cystathionine gamma-lyase (CTH or CSE) inhibitor DL-propargylglycine (PAG, 1 mM). NO synthase inhibitor L-NG-nitroarginine methyl ester (L-NAME, 30 mg/kg, 7 days) was administered before the isolation. The hearts were homogenized for biochemical and molecular analysis. Results: NaHS reversed I/R-induced cardiac performance impairment, increased tissue nitric oxide production and decreased tissue markers for cardiac injury, while L-NAME inhibited these effects. The expression of CTH was increased with PAG, which was suppressed by L-NAME. Conclusion: H(2)S and NO increase each other’s production suggesting their interaction and cooperation in cardioprotection against I/R injury.